274 Characteristics and clinical outcomes of patients with recurrent microsatellite stable endometrial cancer undergoing early phase immunotherapy clinical trials. (13th November 2020) - How, J; Jazaeri, A; Fu, S; Rodon Ahnert, J; Gong, J; Meric-Bernstam, F
Abstract : Introduction: Describe characteristics and outcomes of patients with recurrent microsatellite stable endometrial cancer (MSS EC) undergoing early phase clinical trials with immunotherapy. Methods: Retrospective evaluation of MSS EC patients receiving ≥1 immunotherapeutic agent(s) in early phase clinical trials at MD Anderson Cancer Center from 6/2014 to 12/2019. Response to treatment was evaluated using RECIST criteria and treatment-related and immune-related adverse events (TRAEs and irAEs, respectively) were graded per trial protocols. Predictors of response and progression free survival were evaluated. Results: Thirty-four MSS EC patients were included. The median age and number of prior lines of systemic therapy was 64 years and three, respectively. The predominant histologic subtype was endometrioid (n = 15) or serous (n = 9). Thirty-three of 34 patients (97.1%) were treated with at least one immune checkpoint inhibitor (ICI) and 24 (76.5%) received combination therapy. Among the 30 evaluable patients, the clinical benefit rate was 30% (n = 9); one partial response and eight stable disease. Seven patients (77.8%) with clinical benefit had an irAE, compared to five non-responders (23.8%). Six patients with clinical benefit were treated with ICI and other class agent(s). Greatest benefit was seen with ICI/PARP inhibitor/anti-VEGF (693 days), ICI/PARP inhibitor (308 days), and ICI/oral tyrosine kinase inhibitor (272 days) combinations. No response was seen in ten (83.3%) and two patients (100%) treated with double and triple ICI agents, respectively. Conclusion: MSS EC tumors do not appear to respond to ICI-only therapies. ICI combination therapy with other class agents and presence of irAEs may be associated with clinical benefit.